Retrospective Evaluation of Clinical Bleeding in Dogs With Anticoagulant Rodenticide Toxicity—A Multi-Center Evaluation of 62 Cases (2010–2020) - Stroope, Sarah; Walton, Rebecca; Mochel, Jonathan Paul; Yuan, Lingnan; Enders, Brittany (Frontiers in Veterinary Science, 2022)
Objective To evaluate the most common locations of hemorrhage in dogs diagnosed with anticoagulant rodenticide intoxication. Animals Dogs presenting with hemorrhage secondary to anticoagulant rodenticide intoxication between at two university veterinary teaching hospitals. Procedures Medical records were searched from the years 2010 through 2020 and all records from dogs treated for hemorrhage secondary to anticoagulant rodenticide intoxication were reviewed. Dogs were diagnosed with anticoagulant rodenticide intoxication based on the combination of known exposure and prolonged coagulation testing, including prothrombin and activated thromboplastin time, or based on gas chromatography-mass spectrometry (GCMS). The diagnosis of hemorrhage was made based on physical exam findings, point-of-care ultrasound findings or radiography. Results Sixty-two dogs met the inclusion criteria and were included in the study. The most common sites of hemorrhage included: pleural space (hemothorax 37%), pulmonary parenchyma (24%), abdomen (24%), skin/subcutaneous (21%), gastrointestinal tract (18%), pericardium (13%), oral cavity (13%), nasal cavity (11%), ocular (8%), and urinary tract (7%). Overall, forty-five dogs (73%) had evidence of cutaneous or mucosal hemorrhage while thirty-three (53%) of dogs had evidence of cavitary hemorrhage. Forty-five percent of dogs had hemorrhage noted at only one site, while 55% experienced hemorrhage at more than one site. The location of hemorrhage and total number of hemorrhagic sites was not associated with survival or transfusion requirement. Conclusions and Clinical Relevance In conclusion, this study highlights that dogs with anticoagulant rodenticide intoxication present with diverse locations of hemorrhage and the majority of dogs had non-cavitary hemorrhage noted.